Mental Health Service Utilization among Black Youth; Psychosocial Determinants in a National Sample - Shervin Assari; Cleopatra Howard Caldwell (MDPI AG, 2017)
Racial disparity in mental health service utilization (MHSU) persists, and youths are not an exception to the underutilization of services. Very limited research has been conducted on the determinants of MHSU among Black youth. Using a national sample of American Black youth, the current study investigated the association between demographic factors, socioeconomic status, psychiatric disorders, and self-rated health (SRH) on MHSU. We also tested the heterogeneity of the effects of SRH and psychiatric disorders based on ethnicity, gender, and their intersection. We used data from the National Survey of American Life-Adolescents supplement (NSAL-A), 2003-2004. The study enrolled 1170 Black youth between 13 and 17 years old including 810 African Americans and 360 Caribbean Blacks. Age, gender, ethnicity, socioeconomic status, SRH, 12-month psychiatric disorders (Composite International Diagnostic Interview modified version), and MHSU (last year) were measured. Logistic regressions were used for data analysis. Ethnicity (odds ratio (OR) = 0.33, 95% confidence interval (CI) = 0.17-0.65), subjective socioeconomic status (OR = 1.43, 95% CI = 1.09-1.88), SRH (OR = 2.45, 95% CI = 1.00-6.37), and psychiatric disorders (OR = 2.17, 95% CI = 1.05-4.48) were associated with MHSU. Age, gender, and objective socioeconomic status were not associated with MHSU. Gender and ethnicity did not interact with SRH and psychiatric disorders on MHSU. Actual and perceived need both universally influence Black youths' likelihood of MHSU, regardless of their ethnicity and gender. Ethnicity and perceived socioeconomic status also play unique roles in MHSU. Future research is needed to understand pathways to MHSU for Black youth who both have and perceive mental health needs. There is also a need to find ways to promote MHSU for those with a need for mental health services.